2015
DOI: 10.5941/myco.2015.43.3.280
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Laccase Genes inPleurotus ostreatusand Biochemical Characterization of Laccase Isozymes Produced inPichia pastoris

Abstract: In this study, transcriptome analysis of twelve laccase genes in Pleurotus ostreatus revealed that their expression was differentially regulated at different developmental stages. Lacc5 and Lacc12 were specifically expressed in fruiting bodies and primordia, respectively, whereas Lacc6 was expressed at all developmental stages. Lacc1 and Lacc3 were specific to the mycelial stage in solid medium. In order to investigate their biochemical characteristics, these laccases were heterologously expressed in Pichia pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 36 publications
(41 reference statements)
3
15
1
Order By: Relevance
“…It is noteworthy that the laccase activity observed in the present MM 3 6 9 12 15 18 MM 3 6 9 12 15 18 study was 80 times higher than the laccase activity of Aeromonas hydrophila NIU01 expressed in E. coli (Ng et al 2013). In addition, the value of laccase activity of this work was 2 times higher than that reported by Park et al (2015), where the Lacc6 gene from P. ostreatus was expressed in P. pastoris, obtaining values of 1560 U/L. The wild strain of P. ostreatus produced 3190 U/L at 144 h of culture (Grandes-Blanco et al 2013), while in this work, the recombinant strain of E. coli produced a similar activity in 19 h. …”
Section: Resultscontrasting
confidence: 47%
See 1 more Smart Citation
“…It is noteworthy that the laccase activity observed in the present MM 3 6 9 12 15 18 MM 3 6 9 12 15 18 study was 80 times higher than the laccase activity of Aeromonas hydrophila NIU01 expressed in E. coli (Ng et al 2013). In addition, the value of laccase activity of this work was 2 times higher than that reported by Park et al (2015), where the Lacc6 gene from P. ostreatus was expressed in P. pastoris, obtaining values of 1560 U/L. The wild strain of P. ostreatus produced 3190 U/L at 144 h of culture (Grandes-Blanco et al 2013), while in this work, the recombinant strain of E. coli produced a similar activity in 19 h. …”
Section: Resultscontrasting
confidence: 47%
“…Laccases from P. ostreatus have only been expressed in eukaryotic systems such as Kluyveromyces lactis, Saccharomyces cerevisiae (Piscitelli et al 2005), Trichoderma reesei (Dong et al 2012), and P. pastoris (Zhang et al 2005;Park et al 2015;RiveraHoyos et al 2015), and to date, there is no report on their expression in a prokaryotic system such as E. coli. This bacterium has been widely used for gene expression because it is genetically characterized, spreads easily in simple media with a high rate of cell growth, and can produce high levels of recombinant protein (Sugantha et al 2010;Wang et al 2014;Wurm et al 2016); thus, it is an interesting alternative for the expression of laccases genes from fungi.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, this is caused by the need for large amounts of the gene product or catalytic subfunctionalization of a particular isozyme. A number of recent papers described the differential expression of laccases as a response to diverse environmental factors [17,18], which most likely require synthesis of laccases with different substrate specificity and kinetic properties [19,20]. When considering numerous copies of laccase genes in many organisms and their diverse functions, subfunctionalization seems more convincing [21].…”
Section: Figurementioning
confidence: 99%
“…2A ). Sequence comparison of these 14 laccase genes with the three most-expressed laccase genes (PO Lacc5, PO Lacc6, and PO Lacc12) in Pleurotus ostreatus [ 12 ] and that expressed mainly in Pycnoporus coccineus (PC-LCC1) [ 13 ] revealed that laccase genes Lcc1–Lcc7 of L. edodes were grouped with PO Lacc6 (a major laccase expressed throughout developmental stages of Pleurotus ostreatus [ 12 ]) and PC LCC1 (the only secreted laccase in Pycnoporus coccineus [ 13 ]) ( Fig. 2B ).…”
Section: Resultsmentioning
confidence: 99%